Genetic algorithms modules in e-lessons system â€œ modern learning theories in reviewâ€ - Al-Bayati, Maha A. (International Journal of Engineering and Technology, 2018)
This paper presents e-lessons system which can generate multiple e-Learning modules (eLMs) based on selected modern theories of learning. The considered case study in this paper is Genetic Algorithms topics. In this paper , methodology of tutorial was considered it is a traditional method and suitable to the scope of this research work. Due to the e-lessons system mechanism , two projects have been accomplished , the first for instructor while the second for candidate. Database was used as a tool to save submission of instructor. The e-lessons system in this research work is aimed at achieving maximization of instructional outcomes , continuous interaction between candidate and computer , effective learning aspects as well as realizing the meaningful learning. In order to achieve the previous goals some selected theories of learning were considered (Ausubel , Spiro , Tolman , Skinner and Landa theories ). Tools used to implement the system are , Tutorial methodology of e-Learning , visual programming , Database and multimedia components. The case study of the research is selected topics of Genetic Algorithm. Results and Conclusion ensured the benefits for instructional outcomes in teaching Genetic Algorithms via e Learning depends on systematic e-lessons System. The Genetic Algorithms in the case study realized the desired goals.